The Far-Reaching Roots of Harlem’s “Second Renaissance” (KULT_online, 2018)
Brian Goldstein’s The Roots of Urban Renaissance: Gentrification and the Struggle over Harlem presents a much-needed addition to existing research on the history of urban redevelopment in New York City and the United States. Goldstein’s book analyzes the complex and often contradictory history of urban redevelopment in Harlem in the second half of the twentieth century. His analysis focuses on a number of influential local organizations that initially intended to shape the neighborhood with radical ideas of “community control” for its majority low-income residents, but over time realized a very different vision: a neighborhood for wealthier residents and private investors. His book is thus at the same time a history of a particular and special urban place in the US and an account of the struggle of African-American city dwellers to retain their place in an increasingly gentrified city.